The cross-section: four designs for the Zaan Corridor (OverHolland, 2017)
The Province of Noord-Holland’s spatial policy will in the decades to come be focused on encouraging public transport. Following on from Maak Plaats! Werken aan knooppuntontwikkeling in Noord Holland [Make Room: working on hub development in Noord-Holland], which sets out the principles guiding that policy, the Province has worked with the research section of the BNA (Federation of Dutch Architects) and Deltas, Infrastructures & Mobility Initaitive (TU Delft) to set up a design study project for the Amsterdam-Heerhugowaard railway line. Ten professional design teams and five student teams from TU Delft took part in this. The results have been published under the title Onderweg! Vijftien ontwerpen voor Transit Oriented Development aan de Zaancorridor [Under way! Fifteen designs for transitoriented development in the Zaan Corridor]. Four of the designs that were produced by the students are presented here. For the work with the students, we adopted a strictly architectural and structural perspective and examined what contribution could be made from that perspective to the investigative design.